2011
DOI: 10.4103/1119-3077.86770
|View full text |Cite
|
Sign up to set email alerts
|

Periapical granuloma associated with extracted teeth

Abstract: Periapical granuloma appears to be a less common periapical lesion in this study compared to the previous reports. In contrast to reports that relate to an acute flare of the lesion with abundant neutrophilic infiltration, this study has shown marked foamy macrophages and lymphocytes at the acute phase, which are significantly associated with the clinical diagnosis of acute apical periodontitis. We recommend the classification of periapical granuloma into early, intermediate, and late stages of the lesion, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
0
11
0
3
Order By: Relevance
“…This result contradicts a previous study by Omoregie et al, who found that dental granuloma was mostly found in males between 21 and 30 years old. 9 Bacterial infections in dental pulp usually cause irreversible pulpitis and pulpal necrosis. The interaction between bacterial infection and the immune system in dental pulp results in the release of numerous mediators through the root canal system and initiates reactions in apical tissues that result in the formation of apical lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result contradicts a previous study by Omoregie et al, who found that dental granuloma was mostly found in males between 21 and 30 years old. 9 Bacterial infections in dental pulp usually cause irreversible pulpitis and pulpal necrosis. The interaction between bacterial infection and the immune system in dental pulp results in the release of numerous mediators through the root canal system and initiates reactions in apical tissues that result in the formation of apical lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to that of Omoregie et al, who found the main dominant cell in the early stages of granuloma was infiltrated by macrophages, foamy cytoplasm, with or without neutrophils, and a few lymphocytes. 9 The condition of irreversible pulpitis or pulpal necrosis along with dental granuloma will increase the rate of acute flare if the pulp and root canals are inadequately disinfected. 11 One study demonstrated the highest distribution of bacteria and bacteria biofilm in the entire root canal system in irreversible pulpitis or pulpal necrosis with dental granuloma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O granuloma, ou lesão apical, é histologicamente, um infiltrado inflamatório basicamente formado por macrófagos, linfócitos, leucócitos e neutrófilos (Ishimi et al,1990;Safavi, Ressomando 1991;Wajant et al,1998, Boyce et al,2005Jurisic et al, 2008, Omoregie et al, 2011Jakovljevic et al,2015;Berar et al, 2016,). Nesse tipo de lesão, há acúmulo de IL-1α e IL-1β (Martinez et al, 2007, Yang et al,2018, sendo a IL-1β predominante em lesões periapicais humanas (Miller et al, 1996).…”
Section: Avaliação Do Sucesso Cirúrgicounclassified
“…Porém, um estudo na Nigéria com 75 biópsias de lesões periapicais sem tratamento endodôntico prévio demonstrou haver 22% de abscessos contra 17% de granulomas, os quais exibiram diferentes estágios de desenvolvimento. Os autores comentaram que provavelmente essa redução do número de granulomas tenha sido em função da retirada de casos previamente tratados endodonticamente(Omoregie et al, 2011). Eubacterium); já as lesões refratárias, nas quais ocorrem frequentemente infecções secundárias, exibem maior quantidade de bactérias Gram-positivas, tais como espécies de Streptococcus, P. micra, espécies de Actinomyces, espécies de Propionibacterium, P. alactolyticus, espécies de Lactobacillus, Enterococcus faecalis e O. uli.…”
unclassified